Recent development of biodegradable synthetic rubbers and bio-based rubbers using sustainable materials from biological sources. Issue 52 (30th November 2022) - Boon, Zhen Hern; Teo, Yin Yin; Ang, Desmond Teck-Chye
Abstract : Recent progress to improve the sustainability and biodegradability of synthetic rubber by incorporating raw materials from biological sources. Abstract : Rubber is an amorphous hyperelastic polymer which is widely used in this modern era. Natural rubber is considered the ultimate rubber in terms of mechanical performance, but over the years, some limitations and challenges in natural rubber cultivation that could result in serious shortages in the supply chain had been identified. Since then, the search for alternatives including new natural and synthetic rubbers has been rather intense. The initiative to explore new sources of natural rubber which started during the 1940s has been reignited recently due to the increasing demand for natural rubber. The commercialization of natural rubber from the Parthenium argentatum and Taraxacum kok-saghyz species, with the cooperation from rubber product manufacturing companies, has somewhat improved the sustainability of the natural rubber supply chain. Meanwhile, the high demand for synthetic rubber drastically increases the rate of depletion of fossil fuels and amplifies the adverse environmental effect of overexploitation of fossil fuels. Moreover, rubber and plastic products disposal have been a major issue for many decades, causing environmental pollution and the expansion of landfills. Sustainable synthetic rubber products could be realized through the incorporation of materials from biological sources. They are renewable, low cost, and most importantly, biodegradable in nature. In this review, brief introduction to natural and synthetic rubbers, challenges in the rubber industry, alternatives to conventional natural rubber, and recent advances in biodegradable and/or bio-based synthetic rubbers are discussed. The effect of incorporating various types of biologically sourced materials in the synthetic rubbers are also elaborated in detail.